S15.4 Re-emergence of lymphogranuloma venereum in Europe and the public health response. (10th July 2011) - Ward, H; de Vries, H J C; van de Laar, M
Abstract : Background: In January 2004, public health officials in the Netherlands noted an outbreak of cases of lymphogranuloma venereum (LGV) among men who have sex with men (MSM). Since then a number of outbreaks and cases have been reported from European countries, North America and Australia. The re-emergence of LGV in this population remains poorly understood yet may have important health consequences. Methods: Several EU countries have reported newly diagnosed cases of LGV to The European Surveillance System and a number of additional countries have reported LGV cases to the Epidemiological Information System on STI (hosted by ECDC). We have synthesised evidence from these surveillance reports together with results of clinical and epidemiological studies to better describe transmission and inform the public health response. Results: An increasing trend of LGV has been reported in several Western European countries. In areas with well-established surveillance, LGV has become a significant and persistent infection in MSM. In the UK, there was a rapid rise in cases from 2009 to 2010, while in Amsterdam numbers continue to fluctuate. The European outbreaks appear to be caused by a single LGV variant (L2b) that has been around for several decades, having been detected in rectal swabs from MSM in San Francisco in 1981. The resurgence of LGV over the past decade is closely linked to the overlapping HIV epidemic which it may in turn fuel. A systematic review of 13 descriptive studies showed the prevalence of HIV in LGV cases ranging from 67% to 100%; compared to MSM with non-LGV chlamydia, there was a significant association between HIV and LGV (OR 8.19, 95% CI 4.68 to 14.33). It is likely that changes in sexual behaviour, including serosorting and unprotected anal sex, and an increase in the size of the HIV positive population, may have created the conditions for an explosive LGV outbreak after decades of quiescence. Conclusion: The on-going LGV epidemic shows no signs of waning and requires a robust public health response. Primary prevention should be developed for MSM with HIV, together with awareness campaigns for the wide range of clinicians who may see men with symptoms. In addition, improved diagnostic methods are needed to allow widespread screening could reduce the infectious pool; they would also allow a better picture of the epidemic to be obtained from countries with limited diagnostic facilities.